Survival and electrotransformation of Pseudomonas syringae strains under simulated cloud-like conditions. Issue 5 (28th April 2017) - Blanchard, Laurine S.; Monin, Anaïs; Ouertani, Hounaïda; Touaibia, Lamia; Michel, Elisa; Buret, François; Simonet, Pascal; Morris, Cindy E.; Demanèche, Sandrine
Abstract: To diversify their genetic material, and thereby allow adaptation to environmental disturbances and colonization of new ecological niches, bacteria use various evolutionary processes, including the acquisition of new genetic material by horizontal transfer mechanisms such as conjugation, transduction and transformation. Electrotransformation mediated by lightning-related electrical phenomena may constitute an additional gene-transfer mechanism occurring in nature. The presence in clouds of bacteria such as Pseudomonas syringae capable of forming ice nuclei that lead to precipitation, and that are likely to be involved in triggering lightning, led us to postulate that natural electrotransformation in clouds may contribute to the adaptive potential of these bacteria. Here, we quantify the survival rate of 10 P. syringae strains in liquid and icy media under such electrical pulses and their capacity to acquire exogenous DNA. In comparison to two other bacteria ( Pseudomonas sp. N3 and Escherichia coli TOP10), P. syringae CC0094 appears to be best adapted for survival and for genetic electrotransformation under these conditions, which suggests that this bacterium would be able to survive and to get a boost in its adaptive potential while being transported in clouds and falling back to Earth with precipitation from storms. Abstract : Lightning discharges in clouds or in soil can promote gene transfer by electroporation in bacteria such as the phytopathogene Pseudomonas syringae .